Pengaruh Pelatihan Dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada KUD Pakis Kabupaten Malang (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Human resource management deals with policies and practices that need to be implemented by managers. Every company organization operates by using all of its resources to be able to produce products, both goods/services that can be marketed. This study aims to determine how the simultaneous influence of training and motivation on employee productivity.In this study, the data analysis used was quantitative data in the form of numbers from calculations and measurements and then analyzed using SPPS 24. The data source was obtained from the results of in-depth interviews with individuals, namely directly between the interviewer and the research respondent.Work Productivity is a comparison between the results obtained (output) with the amount of resources used as input (input). In general, work productivity can be interpreted as the output value in its interaction and interrelation with the unity of input values. Employee productivity is usually expressed as a balance of the average results achieved by the workforce, during the working hours available in production.Training and motivation have a simultaneous effect on work productivity, training has no significant effect on work productivity and motivation has a significant effect on work productivity. Keywords: Work Productivity, training and motivation, Human Resource Management